2009
DOI: 10.1158/1055-9965.epi-08-0962
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and Cytokine Receptor Single-Nucleotide Polymorphisms Predict Risk for Non–Small Cell Lung Cancer among Women

Abstract: Studies on the relationships between inflammatory pathway genes and lung cancer risk have not included African-Americans and have only included a handful of genes. In a population-based case-control study on 198 African-American and 744 Caucasian women, we examined the association between 70 cytokine and cytokine receptor single-nucleotide polymorphisms (SNPs) and risk of non–small cell lung cancer (NSCLC). Unconditional logistic regression was used to estimate odds ratios and 95% confidence intervals in a dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…Taken together, the previous (Colakogullari et al 2008; Gu et al 2008; Seow et al 2006; Van Dyke et al 2009) and present studies suggested that none of the three functional IL-6 promoter polymorphisms (-174G>C, -572C>G and -6331T>C) are associated with risk of lung cancer in the Chinese population. However, when performing haplotype-based analyses, we found that the CC (-6331C and -572C) IL-6 promoter haplotype was significantly associated with increased lung cancer risk.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Taken together, the previous (Colakogullari et al 2008; Gu et al 2008; Seow et al 2006; Van Dyke et al 2009) and present studies suggested that none of the three functional IL-6 promoter polymorphisms (-174G>C, -572C>G and -6331T>C) are associated with risk of lung cancer in the Chinese population. However, when performing haplotype-based analyses, we found that the CC (-6331C and -572C) IL-6 promoter haplotype was significantly associated with increased lung cancer risk.…”
Section: Discussionsupporting
confidence: 80%
“…Several investigations have shown that the -174G>C polymorphism contributes to the pathogenesis of colorectal cancer (Landi et al 2003; Slattery et al 2009) and Kaposi sarcoma (Foster et al 2000; Gazouli et al 2004). However, molecular epidemiologic studies have not shown an association between this functional polymorphism and lung cancer susceptibility in the European population (Campa et al 2004, 2005; Colakogullari et al 2008; Engels et al 2007; Seifart et al 2005; Van Dyke et al 2009). Our metaanalysis of 83 studies involving 44,735 cases and 60,747 controls did not show a significant association between the -174G>C polymorphism and cancer risk, including lung cancer (Liu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected on a number of risk factors for NSCLC have been published previously. 2124 NSCLC diagnoses dates, histology, and treatment data were collected through the Metropolitan Detroit Cancer Surveillance System.…”
Section: Methodsmentioning
confidence: 99%
“…IL1, IL1B, IL1RN, TNFA, IL8, COX2, and IL10 SNPs have been associated with risk of lung cancer (43,(46)(47)(48)(49)(50)(51)(52)(53). In the Detroit lung cancer case-control study, associations between lung cancer risk and SNPs varied by race and by history of COPD (54). SNPs in IL7R, IL15, TNF, TNFRSF10A, IL1RN, and IL1A were associated with lung cancer risk in women with self-reported COPD but not among women without COPD.…”
Section: Candidate Gene Studiesmentioning
confidence: 97%